OSTRÁCODOS (ARTHROPODA, CRUSTACEA) DE LA FORMACIÓN LAS ESCOBAS (HOLOCENO), CUENCA DEL SALADO, PROVINCIA DE BUENOS AIRES, REPÚBLICA ARGENTINA (Ameghiniana, 2014)
Twelve ostracod species are identified from Cerro de la Gloria and Canal 18 Members which, in the analysed locality, have been found for the first time superimposed, although separated by a discontinuity. Las Escobas Formation has been deposited in a marginal marine environment; the Cerro de la Gloria Member indicates partially restricted environmental conditions such as a slightly hypohaline lagoon of decreasing energy; the Canal 18 Member was environmentally restricted, with hypoxic conditions, otherwise evidences of increasing environmental energy are registered. Lithology and taphonomic features of macrofossils indicate cycIical altemations of increasing-decreasing water energy.